Elucidation of Charge Contribution in Iridium-Chelated Hydrogen-Bonding Systems - Balónová, Barbora; Blight, Barry A. (Frontiers in Chemistry, 2021)
We present two iridium complexes 1H+ and 2H+ that contain cationic ligands to extend the knowledge of charge-assisted hydrogen bonding (CAHB), which counts among the strongest non-covalent bonding interactions. Upon protonation, both complexes were converted into new hydrogen-bonding arrays with various selectivity for respective H-bonding partners. This study compares the association strengths of four hydrogen-bonding co-systems, emphasizing the roles of CAHB in supramolecular systems. We determined that the cationic charge in these systems contributed up to 2.7 kJ mol-1 in the H-bonding complexation processes.